1996
DOI: 10.1093/beheco/7.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Begging, food provisioning, and nestling competition in great tit broods infested with ectoparasites

Abstract: Ectoparasites are a ubiquitous environmental component of breeding birds, and it has repeatedly been shown that hematophagous ectoparasites such as fleas and mites reduce the quality and number of offspring of bird hosts, thereby lowering the value of a current brood. Selection acting on the hosts will favor physiological and behavioral responses that will reduce the parasites' impact. However, the results of the few bird studies that addressed the question of whether parasitism leads to a higher rate of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(212 citation statements)
references
References 28 publications
7
200
5
Order By: Relevance
“…Because ectoparasites may strongly modify the amount of parental effort [35,36], all nests were treated twice with a microwave appliance in order to kill all ectoparasites inhabiting the nest (see [37]). …”
Section: Methodsmentioning
confidence: 99%
“…Because ectoparasites may strongly modify the amount of parental effort [35,36], all nests were treated twice with a microwave appliance in order to kill all ectoparasites inhabiting the nest (see [37]). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that it is possible that females and males respond to different components of nestling behaviour and phenotype, for example colour (Jourdie et al 2004, de Ayala et al 2007Ewen et al 2008;Galvan et al 2008;Tanner and Richner, 2008), size (reviewed in Slagsvold, 1997;Lessells, 2002), condition (e.g. Christe et al 1996) or visual vs. vocal cues of begging (Kilner, 2002, reviewed in MĂŒller et al, 2007a. We studied whether yolk androgens could mediate sexual conflict over parental care in a small passerine bird, the collared flycatcher (Ficedula albicollis) by conducting two experiments.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…First, a negative correlation between DG densities and nestling body mass may be obscured by parental quality (Bauchau 1997) or by increased begging behaviour of parasitised nestlings, which leads to increased parental provisioning, as was found in the Great Tit (Parus major; Christe et al 1996). Bauchau (1997) found that mite densities did not directly influence body mass in Pied Flycatchers (Ficedula hypoleuca) and suggested that parental quality may have been influencing nestling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Since ectoparasites have been shown to slow nestling growth and development, those nestlings exposed to high parasite densities may therefore reach their maximum weight later and may have more and prolonged parental food provisioning than nestlings exposed to low parasite densities (e.g. Christe et al 1996). In our case, this would mean that Starling nestlings exposed to low ectoparasite densities may reach their maximum mass at first measurement (day 10), and those exposed to high ectoparasite densities may reach their maximum mass later, i.e.…”
Section: Discussionmentioning
confidence: 99%